ANALISIS AKUNTANSI SYARIAH SEBAGAI SISTEM INFORMASI DI INDONESIA (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
Accounting is an information system that identifies, records, summarizes, classifies, and reports data related to economic events to enable users to make informed decisions. While in sharia accounting, the word 'sharia' generally means the path that we must go through. A Muslim certainly cannot escape from Islam. after saying the shahada, he must follow the rules of Allah and the Messenger,